2020
DOI: 10.1101/2020.04.06.027805
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequence-based prediction of vaccine targets for inducing T cell responses to SARS-CoV-2 utilizing the bioinformatics predictor RECON

Abstract: BackgroundThe ongoing COVID-19 pandemic has created an urgency to identify novel vaccine targets for protective immunity against SARS-CoV-2. Consistent with observations for SARS-CoV, a closely related coronavirus responsible for the 2003 SARS outbreak, early reports identify a protective role for both humoral and cell-mediated immunity for SARS CoV-2.MethodsIn this study, we leveraged HLA-I and HLA-II T cell epitope prediction tools from RECON® (Real-time Epitope Computation for ONcology), our bioinformatic p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Predicted 9-11 mer epitopes from the following open reading frames (ORFs) of the SARS-CoV-2 proteome were included in the analysis: ORF 1ab, 3a, 6, 7a, 7b, 8, 9b, 10, 14, envelope (E), membrane (M), nucleoprotein (N) and spike (S) protein. In addition, SARS-CoV-2 epitopes that were predicted to be most immunogenic by the science community were included for analysis (Table S1) [48][49][50][51] .…”
Section: Sars-cov-2 Epitope Selection and Peptide Synthesismentioning
confidence: 99%
“…Predicted 9-11 mer epitopes from the following open reading frames (ORFs) of the SARS-CoV-2 proteome were included in the analysis: ORF 1ab, 3a, 6, 7a, 7b, 8, 9b, 10, 14, envelope (E), membrane (M), nucleoprotein (N) and spike (S) protein. In addition, SARS-CoV-2 epitopes that were predicted to be most immunogenic by the science community were included for analysis (Table S1) [48][49][50][51] .…”
Section: Sars-cov-2 Epitope Selection and Peptide Synthesismentioning
confidence: 99%
“…These features confer unique properties to the epitope maps that underlie our epitope hotspot predictions and digital twin optimization. These properties differ from the SARS-CoV-2 epitope maps that have been reported in recent preprints since the outbreak of this virus, which mainly utilize predictions based on HLA binding [29][30][31].…”
Section: Discussionmentioning
confidence: 87%
“…Taken together, this supports the approach taken in this study, which is to map computationally, a broad epitope landscape across the global viral SARS-CoV-2 proteome, which includes integrated CD8, CD4 and B cell targets in the modeling. There has been some preliminary efforts submitted into preprint servers recently that describe epitope maps generated [29][30][31], however it appears that the emphasis in those approaches were based mostly on HLA binding. It is important to profile in whole viral proteome epitope screens, as carried out in this study using an extensive artificial intelligence platform, not only the candidates that may bind to the HLA molecule but also those CD8 epitopes that are naturally processed by the cell's antigen processing machinery, and presented on the surface of the infected host cells.…”
Section: Introductionmentioning
confidence: 99%
“…The data features both linear epitopes recognized by B-cell receptors or antibodies as well as information on conformational epitopes (Pinto et al, 2020;Yuan et al, 2020) (recorded in Crowd-sourced annotations track, data not shown). These tracks also display epitopes recognized by CD8-positive or CD4-positive T-cells when presented by HLA molecules on host cells (Grifoni et al, 2020a;Poran et al, 2020) . Where possible, the latter are organized according to the HLA allele of the host used in their presentation.…”
Section: Uniprot Protein Annotationsmentioning
confidence: 99%